Relationship among financial literacy, attitude and retirement planning awareness: A PLS-SEM approach / Salwa Muda… [et al.] - Muda, Salwa; Musman, Musliha; Hussin, Amariah Hanum; Idris, Asma’ Rashidah; Zainal Abidin, Nurain Farahana; Kamarulzaman, Masrul Hayati; Mohd Zaid, Noor Azila (2023)
A retirement plan is designed to take care of post-retirement days and help retirees to enjoy a stress-free life. Having a good financial retirement plan facilitates individuals to live the lifestyle they desire as retirees. It is crucial for the young generation to be aware of retirement planning to appropriately plan for their retirement. However, university students have lack of awareness on the significance of early retirement planning and future savings planning due to limited knowledge and attitude. Thus, this study was carried out to identify the relationship between financial literacy and attitude towards retirement planning awareness among students in Universiti Teknologi MARA Negeri Sembilan. Questionnaires were distributed to a total of 171 students from three campuses namely Kuala Pilah, Seremban, and Rembau responded to the questionnaires. Data was further analyzed using PLS-SEM analysis through measurement and structural analysis. The study indicates that financial literacy and attitude have significant and positive effects on retirement planning awareness. This study provides students with valuable insights into the importance of financial literacy and positive attitudes towards retirement planning. The respondents of the study only comprised of small sample size; students from three campuses in UiTM Negeri Sembilan, thus limit the generalizability of the findings. Secondly, the usage of questionnaire in gathering data limits the information obtained for the analysis. Additionally, the number of contributing factors influencing retirement planning among university students were limited, thus might not reflect the overall factors of retirement planning. The study has significant implication that align with various Sustainable Development Goals (SDGs) by addressing financial literacy and retirement planning attitudes among university students, ultimately contributing to a more equitable, informed, and economically secure society. Improved financial literacy and retirement planning attitudes could contribute to reducing the risk of future poverty among individuals, aligning with SDG 1 (No Poverty). The combination of financial literacy and a positive attitude towards retirement planning empowers individuals to make informed decisions, understand diverse investment strategies, manage debt responsibly, save effectively and adapt to changing of financial market and economic condition. Furthermore, highlighting the lack of financial literacy among university students emphasizes the need for incorporating financial education into curriculum, promoting a holistic quality education that prepares students for real-world challenges which parallel to SDG 4. Thoughtful actions should be taken by policymakers to ensure the goals are achieved and students will be able to gain benefits from it. This study quantifies evidence that students are aware on the importance of retirement planning. The outcomes of the research are useful to decision makers in providing awareness and programs that will help young generation to start saving for their future.